Calculation method of active power output of wind farms connected to grids based on FRC - Ning Chen; Yun Zhang (2010 Chinese Control and Decision Conference, 2010)
A new method to calculate active power output of large-scale wind farms connected to power grids, based on the fuzzy random chance-constrained programming(FRC )theory, is presented in this paper. The calculation of calculate active power output can be turned into a FRC programming problem which constrained conditions. A mathematical model of calculate active power in wind power integrated system based on FRC programming form is put forward, including ramp constrains of the generating units, output restricted zone, line transmission capacity, reserved capacity constraints, the balance of load, and so on. The problem can be solved by particle swarm optimization based fuzzy simulations. The results on IEEE30 system demonstrate the advantages of the proposed approach.